Spatial mapping of ectonucleotidase gene expression in the murine urinary bladder - Aresta Branco, Mafalda S. L.; Perrino, Brian A.; Mutafova-Yambolieva, Violeta N. (Frontiers in Physiology, 2023)
Purinergic signaling is important for normal bladder function, as it is thought to initiate the voiding reflex and modulate smooth muscle tone. The availability of adenine nucleotides and nucleosides (aka purines) at receptor sites of various cell types in the bladder wall is regulated by ectonucleotidases (ENTDs). ENTDs hydrolyze purines such as adenosine 5'-triphosphate (ATP) and adenosine 5'-diphosphate (ADP) with varying preference for the individual substrate. Therefore, the end effect of extracellular purines may depend significantly on the type of ENTD that is expressed in close proximity to the target cells. ENTDs likely have distinct cellular associations, but the specific locations of individual enzymes in the bladder wall are poorly understood. We used RNAscope™, an RNA in situ hybridization (ISH) technology, to visualize the distribution and measure the levels of gene expression of the main recognized ectonucleotidases in large high-resolution images of murine bladder sections. The relative gene expression of ENTDs was Entpd3 > Alpl >> Enpp1 = Entpd2 >> Enpp3 > Entpd1 (very low to no signal) in the urothelium, Entpd1 ≥ Entpd2 >> Enpp3 > Enpp1 = Alpl ≥ Nt5e (very low to no signal) in the lamina propria, and Entpd1 >> Nt5e = Entpd2 >> Enpp1 > Alpl = Enpp3 in the detrusor. These layer-specific differences might be important in compartmentalized regulation of purine availability and subsequent functions in the bladder wall and may explain reported asymmetries in purine availability in the bladder lumen and suburothelium/lamina propria spaces.